The effects of social media on investment decision - Agrawal, Ayushi (2023)
Although the field of finance has been studied for some time, behavioural finance, which examines how psychological factors can affect market results, is still relatively uncharted territory. Numerous research has been conducted on this topic since social media, which has rapidly expanded and is now an essential component of daily life, is acknowledged as being essential to forecasting future events. On the other hand, there hasn't been a lot of study on how social media material affects other time-dependent real-life occurrences. By analyzing the connection between social media and investing choices, this study seeks to fill this vacuum in the literature. To better understand the role of social media in investment decisions, this study will analyze the dimensions of social media: the information obtained from social media, and the behavior of social media users. The research employs a quantitative method. First approach is collecting data through questionnaires created with Google forms and analyzing it using a binomial distribution test in Microsoft excel software. The second approach was by using secondary data i.e., we gathered data from yahoo finance regarding the stock price of the companies and from Google trends regarding Google trend search volumes and YouTube trend search volumes then analyzing it using linear regression in Microsoft Excel software. The findings of this study reveal a positive correlation between these independent variables and the dependent variable, indicating that social media does indeed have an impact on investment decisions. This study aims to contribute to the literature on a relevant and timely topic, exploring the influence of social networks on capital market movements. Its findings have the potential to inform future research on financial behavior and decision-making.